2008
DOI: 10.1152/ajprenal.00454.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of febuxostat on metabolic and renal alterations in rats with fructose-induced metabolic syndrome

Abstract: Increased fructose consumption is associated with hyperuricemia, metabolic syndrome, and renal damage. This study evaluated whether febuxostat (Fx), an investigational nonpurine, and selective xanthine oxidase inhibitor, could alleviate the features of metabolic syndrome as well as the renal hemodynamic alterations and afferent arteriolopathy induced by a high-fructose diet in rats. Two groups of rats were fed a high-fructose diet (60% fructose) for 8 wk, and two groups received a normal diet. For each diet, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
105
3
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 164 publications
(127 citation statements)
references
References 56 publications
12
105
3
7
Order By: Relevance
“…In that study, the dehydration procedure was severe (34). We have also shown that a 60% fructose diet induces renal damage in the course of 8 wk (36). Moreover, rats that received a similar FG beverage ad libitum developed mild renal damage; however, those animals ingested ϳ80 ml of this fluid per day (39) in contrast to the present study in which rats had a limited consumption of this sweetened beverage (12 ml/day).…”
Section: Discussioncontrasting
confidence: 73%
“…In that study, the dehydration procedure was severe (34). We have also shown that a 60% fructose diet induces renal damage in the course of 8 wk (36). Moreover, rats that received a similar FG beverage ad libitum developed mild renal damage; however, those animals ingested ϳ80 ml of this fluid per day (39) in contrast to the present study in which rats had a limited consumption of this sweetened beverage (12 ml/day).…”
Section: Discussioncontrasting
confidence: 73%
“…In rodents, fructose, unlike other sugars, induces hyperuricemia (115,132) which is a major risk factor for hypertension (50). Recent clinical studies using patient data from the Third National Health and Nutrition Examination Survey confirm the link not only between hyperuricemia and hypertension in particular but also between serum concentrations of uric acid and the prevalence of metabolic syndrome in general (29,53).…”
Section: Pathology and Glut5mentioning
confidence: 99%
“…In animal studies, lowering urate reduced glomerular hypertension, preserved renal function, and decreased tubulointerstitial fibrosis, supporting a potential causal role of hyperuricemia in kidney disease (35,38). If a causal relationship exists, urate might also be useful in identifying individuals at substantial risk for AKI, particularly AKI that occurs in the setting of hemodynamic instability or tubulointerstitial damage.…”
Section: Discussionmentioning
confidence: 91%